2015
DOI: 10.15744/2455-7641.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Hematopoiesis in a Non-Transfused Elderly Patient Diagnosed with Beta Thalassemia Minor

Abstract: Extramedullary hematopoiesis (EMH) is a compensatory reaction caused by the presence of hematopoietic precursors outside the bone marrow, ineffective erythropoiesis and patients with chronic hemolytic anemia. The most frequent cause of EMH is thalassemia intermedia, that produces an increase in demand of the hematopoietic system caused by anemia and is not reduced by transfusion therapy. We present a case of a man of 63 years with beta thalassemia minor, who had not received any transfusion, and that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Despite extensive literature search, to the best of our knowledge there are only two cases reported in literature of SCC due to EMH in patients with Thalassemia Minor. Beunasmananas -cervantas D reported a case of a 63 year old male with beta Thalassemia Minor with SCC caused by EMH [9] . Lalueza A et al reported case of presacral and intrathoracic EMH in a 64 year old male with Thalassemia Minor [10] .…”
Section: Case Reportmentioning
confidence: 99%
“…Despite extensive literature search, to the best of our knowledge there are only two cases reported in literature of SCC due to EMH in patients with Thalassemia Minor. Beunasmananas -cervantas D reported a case of a 63 year old male with beta Thalassemia Minor with SCC caused by EMH [9] . Lalueza A et al reported case of presacral and intrathoracic EMH in a 64 year old male with Thalassemia Minor [10] .…”
Section: Case Reportmentioning
confidence: 99%